Stressor pileup, family and couple relational well‐being, and parent stress during the COVID‐19 pandemic - Anis Ben Brik (19239442) (2023)
Objective The goal was to explore mechanisms linking cumulative stressors with parent stress during COVID‐19. Background Public health measures helped contain COVID‐19 spread, but disrupted family life and increased parents' stress. Positive family relationships and beliefs about the impact of challenges can foster psychological resilience during adversity and may influence parents' stress. Method Participants included parents from the U.S. sample of the internet‐based Covid Family Life Study survey who indicated they were married or living with a romantic partner (n = 1,386). We tested a moderated mediation model predicting parent stress from the pileup of stressors, family and couple relationship satisfaction, and parent resilience beliefs. Results High stressor pileup was associated with lower family and couple relationship satisfaction, and higher parent stress. Relationship satisfaction mediated the effect of stressor pileup on parent stress, and the indirect effects were similar across all levels of parent resilience beliefs. Family satisfaction mediated the effect of stressor pileup on parent stress only for parents with low resilience beliefs. Parent resilience beliefs moderated the relations between relational well‐being and parent stress. Higher family satisfaction was associated with lower stress for parents with low and moderate levels of resilience beliefs, but higher stress for parents with high resilience beliefs. Conclusion Relationship satisfaction may explain how stressor pileup affects parent stress. Resilience beliefs may affect the explanatory role of family satisfaction. Implications Interventions to improve family satisfaction may be most impactful for parents who have low confidence in their ability to adapt to change and bounce back from adversity. Other Information Published in: Family Relations License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/fare.12982